2019
DOI: 10.1186/s42490-019-0004-1
|View full text |Cite
|
Sign up to set email alerts
|

BMC Biomedical Engineering: a home for all biomedical engineering research

Abstract: This editorial accompanies the launch of BMC Biomedical Engineering, a new open access, peer-reviewed journal within the BMC series, which seeks to publish articles on all aspects of biomedical engineering. As one of the first engineering journals within the BMC series portfolio, it will support and complement existing biomedical communities, but at the same time, it will provide an open access home for engineering research. By publishing original research, methodology, database, software and review articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In contrast, 3D cell culture not only mimics the 3D structure of the bone tissue but can also positively influence osteogenic differentiation of MSCs whilst simultaneously reducing their cellular senescence [ 34 ]. MSCs of different tissue origin have been successfully cultivated in a multitude of different solid 3D scaffolds and hydrogels including calcium phosphate ceramic [ 35 ], apatite-wollastonite [ 36 ], poly(ε-caprolactone) [ 37 ], alginate [ 38 ] collagen [ 39 ], Matrigel [ 40 ], bacteria-derived cellulose [ 41 ], and methylcellulose [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 3D cell culture not only mimics the 3D structure of the bone tissue but can also positively influence osteogenic differentiation of MSCs whilst simultaneously reducing their cellular senescence [ 34 ]. MSCs of different tissue origin have been successfully cultivated in a multitude of different solid 3D scaffolds and hydrogels including calcium phosphate ceramic [ 35 ], apatite-wollastonite [ 36 ], poly(ε-caprolactone) [ 37 ], alginate [ 38 ] collagen [ 39 ], Matrigel [ 40 ], bacteria-derived cellulose [ 41 ], and methylcellulose [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated tendon length changes from GM muscle fascicle and MTU length changes taking the ankle and knee joint angles into account 44 . This assumes that the aponeurosis is of equal stiffness as the free tendon, and does not contribute to the storage and return of elastic energy, which may not be true 45 , 46 , and could change with the level of muscle activation 47 . Thus, we have likely underestimated the total amount of energy return by the AT (and aponeurosis), particularly in instances where AT force was high.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant loss of visual quality when applying spiral sampling to 4D Flow MRI in the aorta, despite the major reduction in scan time it provides, according to the included studies [ 10 , 22 ]. Compressed sensing has been stated to have no significant effect on visual quality when not overused; however, it does increase computational complexity, thereby potentially increasing the reconstruction time of the acquired image data [ 35 ]. The two included studies which combined spiral sampling and compressed sensing demonstrated that 4D Flow MRI with spiral sampling and compressed sensing can be applied in the abdominal veins, with greatly reduced scan time compared to radial sampling with or without k-t GRAPPA and cartesian sampling, and still maintain a good vascular conspicuity and strong agreement of the acquired quantitative parameters with those from established techniques [ 10 , 22 ].…”
Section: Discussionmentioning
confidence: 99%